Effect of Anti-tubercular Drugs and Impact of Glycemic Status in Patients with Tuberculosis and Concomitant Diabetic- Tuberculosis Patients - John, Nimmy Njattmkalayil; George, Jane Mary; Poornachary, Narmadha Mukunda (Indian Journal of Pharmacy Practice)
India is a key nation which is endemic and epidemic to tuberculosis and diabetes. An association between diabetes and TB is biological plausible, where diabetes impairs the immune system and making it harder for the body to fight against infection. Methodology: Patients on DOTS therapy in continuation phase of anti-TB therapy, Patients with TB and Diabetes and Patients with TB alone were included in the study. Blood samples were collected and Fasting Blood Glucose (FBG), Post Prandial Glucose (PPG) and Glycated Hemoglobin (HbA1c) were measured to understand the glycemic status and its impact on TB treatment outcomes. Results: Our study confirms the fact that type II diabetes is a strong risk factor for tuberculosis and is associated with a slower response to TB treatment and a higher mortality rate. Incidence of TB is greatest among those with conditions impairing immunity such as DM. Diabetes impairs the immune system, making it harder for the body to fight against infection.
Keywords: Tuberculosis; Glycemic status; Lung field; Diabetes Mellitus; Glycated Hemoglobin